Obtención de Proteína Unicelular a partir de la Fermentación del Suero Ácido de Quesería - Galán Robalino, Paola Andrea (2020)
This research was based on the use of acid cheese serum for obtaining single-cell protein through Kluyveromyces marxianus yeast. The use of whey as a by-product helps not only to reduce organic matter, but also to obtain substances with a higher added value. It is because its large amount of protein nutrients. There were three treatments as part of the methodology which included different types of whey such as: mozzarella cheese, fresh cheese and cottage cheese and two repetitions. The different sera used as a substrate for fermentation underwent physicochemical analyzes before and after the addition of minerals. For the protein analysis, the kjeldahl method is used. It allowed obtaining the following results: 6.95% for mozzarella cheese whey, 6.41% for cottage cheese whey, and 10.4% for fresh cheese whey (N * 6.38). The fermentation process to obtain biomass of Kluyveromyces marxianus took place at a temperature of 39 ° C. In the ash content, no differences were found, since the same amount of minerals will be placed in the three types of treatments. The acidic pH ranges from 4 to 5. It is essential for obtaining proteins, the acidity, the temperature, a correct agitation of the serum, and the use of yeasts in order to obtain a single-cell protein.